Comparative effects of corrosion on electroless -nickel plated A6061 alloys in DOT3 brake fluid - O. Ajibola, Olawale; A.Olubambi, Peter (International Journal of Engineering and Technology, 2018)
Aluminium alloys used in automobile brake master cylinder pistons wear by corrosion due to contamination and chemical reaction of the contacting brake fluid. The study investigates the corrosion of electroless-nickel (EN) deposition enhanced cast aluminium alloy master cylinder piston surfaces immersed in hydraulic brake oil. Cast specimens were produced from the as-received wrought A6061 alloy scrap by sand casting. EN plated as-received and cast aluminium alloys specimens were immersed fully in brake oil for 1680 hours and corrosion rates were determined every 24 hours. Test samples were characterised using the hardness tester, atomic absorption spectrometer, metallurgical photo-microscope, x-ray diffractometer; and SEM with EDX attachment. Both surfaces corroded in the order of electroless-nickel plated cast aluminium alloy (ENCA) < electroless-nickel plated as-received aluminium alloy (ENAA) at 0.0235 and 0.0251 rates (mg/mm2/y) results which showed improvement in the corrosion resistance with significant influence of electroless-nickel coating in reducing corrosion rates of aluminium alloy in brake oil.Â Â